Concordance of Stress Among Married Couples in Urban Area of Nagpur, Maharashtra, India - Sanjeev M. Chaudhary; Sanjay S. Kubde; Ujwala Ukey; Uday Narlawar (Journal of Preventive Medicine And Care, 2019)
Background Concordance or husband wife agreement on various factors like sleep, substance use, dietary supplement use, and diseases like obesity and hypertension has been extensively studied worldwide. But the data regarding concordance of stress among married couples in India is lacking. Objective The prime objective of this study was to find out proportion of concordance of stress among married couples in Nagpur, Central India. Methods This was a community based cross sectional study conducted in an urban area of Nagpur. 260 couples in whom both husband and wife were of the age 30 years or more were included. Stress among couples was assessed by Presumptive stressful life events scale (PSLES). Results 82.3% concordance of stress was observed. Getting married, birth of daughter, death of close family member, illness of family member, gain of new family member and going on pleasure trip or pilgrimage were most common events reported by both spouses. Pregnancy of wife was the most common event reported by husbands. Four husbands reported death of spouse as a life event. None of the spouses reported extra marital relation of spouse and conflict over dowry as life time events. Conclusions Concordance of stress was very high among couples. This suggests role of shared marital environmental factors, which could affect stress concordance among couples.
Keywords: Concordance